Crystallization and X-ray crystallographic analysis of the cap-binding domain of influenza A virus H1N1 polymerase subunit PB2 - Liu, Yong (International Union of Crystallography, 2013)
PB2 is one of the subunits of the influenza virus heterotrimeric polymerase. By its cap-binding domain (PB2(cap)), PB2 captures the 5′ cap of the host pre-mRNA to generate a capped 5′ oligonucleotide primer for virus transcription. The crystal structure of influenza A virus H3N2 PB2(cap) with bound cap analogue m(7)GTP has been reported previously. To show the substrate-free structural details of PB2(cap) and clarify whether obvious conformational changes exist between the substrate-free and substrate-bound cap-binding domain, we have successfully obtained the crystal of substrate-free H1N1 PB2(cap). The crystal of H1N1 PB2(cap) diffracted to a high resolution of 1.32 Å. The crystal symmetry belongs to space group P1 with unit-cell parameters a = 29.49, b = 37.04, c = 38.33 Å, α = 71.10, β = 69.84, γ = 75.85°. There is one molecule in the asymmetric unit.